Using of Remote Sensing and Geographic information Systems Applications in studying the Hydrogeomorphology of the NEOM project coast between Ras Sheikh Hamed in the north and Ras Sharma in the south - Aljuraysi, Najat Hamad; Aldughairi, Ahmed Abdullah (Journal of natural sciences, life and applied sciences, 2022)
The use of remote sensing and geographic information systems applications in the study of the hydrogeomorphology of the Neom coast between Ras Al- Sheikh Hamid in the north to Ras Sharma in the south.The research dealt with the use of remote sensing applications and geographic information systems in the study of the hydrogeomorphology of the Neom coast between Ras El Sheikh Hamid in the north to Ras Sharma in the south, it also gained its importance from the region's diversity in geomorphological phenomena, and it aimed to study the natural characteristics affecting the study area, and to highlight the role of remote sensing techniques in modeling the coastline, and geomorphological phenomena. The study used the descriptive analytical approach which depends on remote sensing techniques (RS) and geographic information systems (GIS) through the automated processing of the data used, which is represented by satellite data to analyze the characteristics of the studied phenomena. It also relied on some methods; Such as surveys, field monitoring, in addition to the method of analyzing satellite visuals to monitor geomorphological phenomena, to create a database of geographical phenomena in the study area.The study found an explanation of the geomorphological phenomena on the coasts of the region and the coastal plain, namely coastal cliffs, active and stable cliffs, sea heads, bays, shrooms, and sidewalks. marine, including coastal lakes; There were three open lakes and one closed lake. Twenty- two islands appeared such as Tiran, Sana fir, Sandala, Al- Farsha, and Al- Taghbaa, including flood fans, valleys, and dunes; Where a database of geographical phenomena has been built, which contributes to the development of the study area, which is a base for sand, vegetation, mountains, soil, valleys, and tourism. The results of the study also showed a discrepancy in the areas of sandy sediments in the study area; It formed in a wide area at Ras Sheikh Hamid, Al- Khubat, and Al- Khuraybah, with an area of 592.7 km² and a rate of 48.57% of the total area in the region. Ras al- Sheikh Hamid and al- Khabat are from the study area, while the study area was characterized by the high mountains, and they were concentrated in the north of the region, the highest of which was Mount Al- Ridda, which reached a height of (339) m, and the lowest in height was Mount Mahadar Ainunah, which had a height of 114 m; Where is it located in Sharma. As for the spatial and distributional characteristics of the soil in the study area; The Camp Orthides soil- which is a deep alluvial soil- formed a large area of the study area, with an area of (418.07) km² and a percentage of (34,26%). Upon morphometric and hydrological analyzes of the drainage basins, we find the tributaries of the drainage basins in the study area with high flows in Wadi Afal; It reached a rate of (3.84), and the lowest was at a rate of (1.38) in Basin (11) and Basin (9), while the tourist attractions and services were concentrated in three areas: Sharma, Khraibeh, and Qayal in the study area.
Keywords: remote sensing applications; GIS; hydrogeomorphology; Neom coast